ИСПОЛЬЗОВАНИЕ КЕЙС МЕТОДА В ОБУЧЕНИИ СТУДЕНТОВ В ОБЛАСТИ ГРАЖДАНСКОГО СТРОИТЕЛЬСТВА (на примере американских ВУЗов) - Ешниязов, Р. (SCIENCE and SOCIETY, 2024)
The article provides an overview of the scientific literature of North American scientists and educators on the application of the case method in teaching engineering disciplines. The distinctive features of using the method in comparison with those used in business or legal education are shown. There is a need for a wider application of this method in the preparation of students in the field of civil engineering.